The Effect of Giving Cucumber Masks against Melasma in Acceptors of Combination Injection Contraception Users at the Independent Midwife Practice in Bungursari, Purwakarta, Indonesia - Intan Noor Khalifah; Noti Feberi Endriani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background. Cucumber is one of the natural ingredients that has been widely used traditionally to maintain facial skin health. Cucumber is rich in antioxidants which have the potential to suppress the inflammatory process that arises due to hormonal imbalances in melasma sufferers due to the use of injectable contraception. This study aimed to determine the effect of using a cucumber mask on the incidence of melasma in acceptors injection contraception users at the independent midwife practice in Bungursari, Purwakarta, Indonesia. Methods. This study was an experimental study in which a total of 30 research subjects participated in this study. Data analysis was carried out using SPSS 25 software in a bivariate manner to determine the effect of using cucumber masks on melasma. Results. After using the cucumber mask on the first day, there was an improvement in melasma in the intervention group compared to before using the cucumber mask, p=0.02 (p<0.05). Likewise, after using the cucumber mask on the second to the seventh day, there was an improvement in melasma in the intervention group compared to before using the cucumber mask, p <0.05. Conclusion. There is an effect of using a cucumber mask on melasma in acceptors of injection contraception users at the independent midwife practice in Bungursari, Purwakarta, Indonesia.